2023
DOI: 10.14202/vetworld.2023.118-125
|View full text |Cite
|
Sign up to set email alerts
|

First meta-analysis study of cholinesterase inhibition in experimental animals by organophosphate or carbamate insecticides under the influence of diphenhydramine

Abstract: Background and Aim: Diphenhydramine is an H1-antihistamine that counteracts the toxic effects of organophosphate and carbamate insecticides that inhibit cholinesterase (ChE) activity. This meta-analysis aimed to investigate the effects of diphenhydramine on ChE inhibition induced by these insecticides in the plasma, erythrocytes, or whole brain of experimental animals. Materials and Methods: A data search was performed on erythrocyte, plasma, and brain ChE inhibition caused by organophosphate and carbamate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…The present meta-analysis of LD50 values indicated that diphenhydramine unequivocally protected experimental animals (mice, rats, and chicks) from the acute toxicity of ChE inhibitors. This result is in agreement with a recent meta-analysis of the antidotal action of diphenhydramine against organophosphate and carbamate insecticides taking into consideration the acute toxidrome of these insecticides, but not their LD50 values [12]. LD50 values of toxicants are excellent indices of their acute toxicity, especially when conducted within 24 hours [31,36].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The present meta-analysis of LD50 values indicated that diphenhydramine unequivocally protected experimental animals (mice, rats, and chicks) from the acute toxicity of ChE inhibitors. This result is in agreement with a recent meta-analysis of the antidotal action of diphenhydramine against organophosphate and carbamate insecticides taking into consideration the acute toxidrome of these insecticides, but not their LD50 values [12]. LD50 values of toxicants are excellent indices of their acute toxicity, especially when conducted within 24 hours [31,36].…”
Section: Discussionsupporting
confidence: 90%
“…The mechanism of ameliorative action of diphenhydramine against ChE inhibitors' intoxication is most probably due to the potent antimuscarinic property of this antihistamine [10][11][12]. There is also a possibility of additional anti-nicotinic and anti-ChE (weak inhibition) actions of diphenhydramine that might contribute to this antidotal action [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations